(untitled) (Research, Society and Development, 2020)
This article presents the report of an experience in a chemistry class in the 3rd year of high school, conducted by a resident scholarship holder of the Pedagogical Residency Program (PRP), in a public school, located on the outskirts of Uruguaiana city - RS. The plan consists of the initial problematization with a textbook in the classroom, a resource available in all schools and was based on the 1st Pedagogical Moment (1PM) of the 3PM, a methodology proposed by Delizoicov, Angotti and Pernambuco (2018). The 1PM consists of verifying the previous knowledge that students have on the subject that will be worked on, so that the knowledge already consolidated can serve as an anchor for the knowledge that will be built, favoring scientific literacy. The objective of this work was to develop the contextualization of the organic chemistry content using the text "Anesthetics" (Fonseca, 2016) through the dynamics of friendly reading during the 1PM and addressing the History and Philosophy of Science (HPS). The program started with the reading of the text, after the reading of each sentence of the text by a different student, an argumentative discussion was held where the students participated actively exposing their previous knowledge, relating the importance of chemistry in medicines and relating it to their daily lives. Through the students’ speeches, it was concluded that 1PM and HPS in the contextualization of the content are important to motivate students in their teaching-learning process.